Captive Breeding and Reproductive Efficiency of Red Junglefowl: Implications for Conservation and Poultry Improvement - Md. Kamruzzaman; Miah, Abdul Gaffar; Osti, Komal Laxmi; Mobarak, Md. Hosne; Salma, Ummay (International Journal of Applied Sciences and Biotechnology, 2025)
The Red Junglefowl (RJF; Gallus gallus) is the wild ancestor of domesticated chickens, holds significant ecological and economic importance. However, habitat destruction, genetic dilution, and declining population numbers necessitate conservation strategies. This study evaluated the productive and reproductive efficiency of RJFs under captive conditions and compared their performance with Indigenous Naked Neck (INN) chickens. A total of 20 RJFs and 20 INNs were reared under semi-intensive conditions. Key parameters such as growth rate, egg production, fertility, hatchability, and egg quality were analyzed. Results indicated that RJFs exhibited distinct phenotypic traits, including vibrant plumage in males and a more compact body structure compared to INNs. RJFs had a significantly lower body weight than INNs, with males averaging 1375.2 g and females 890.5 g. They exhibited delayed sexual maturity, reaching the point of lay at 218.4 days compared to 135.0 days in INNs. However, RJFs demonstrated promising reproductive potential, with a fertility rate of 76.00% and hatchability of 57.89%, slightly higher than that of INNs. RJF eggs were smaller (42.1 g) but exhibited superior internal quality, reflected by a significantly higher Haugh unit score (71.98) compared to INN eggs. The findings suggest that while RJFs are not optimized for high egg production, their genetic traits, including superior egg quality, adaptability, and disease resistance, could be beneficial for breeding programs. Conservation efforts incorporating RJFs into sustainable poultry farming could support biodiversity while offering economic opportunities for smallholder farmers. Future research should focus on selective breeding strategies to enhance their productivity and explore their potential in free-range. Int. J. Appl. Sci. Biotechnol. Vol 13(2): 87-93.